Shivering control in women under spinal anesthesia: A narrative review on the role of drugs - Mehrdad Malekshoar; Majid Vatankhah; Athar Rasekh Jahromi; Hamed Ghasemloo; Farideh Mogharab; Mojtaba Ghaedi; Samaneh Abiri; Lohrasb Taheri; Davoud Roostaei; Navid Kalani; Naser Hatami; Seyed Ebrahim Sadeghi (Mashhad University of Medical Sciences, 2021)
Introduction: Prevention and control of maternal shivering during spinal anesthesia for cesarean section is very important in the appropriate outcomes of surgery; however, choosing the appropriate drug for this issue should be associated with few side effects for mother and baby. Therefore, this study was performed with aim to evaluate the drugs used to control shivering in women under spinal anesthesia.Methods: In this narrative review study, to find the related studies, computer search was performed in databases of SID, Magiran and Google Scholar with Persian keywords of spinal anesthesia, shivering and cesarean section. In the initial stage of searching, 364 studies were reviewed and 341 studies were deleted due to not being related to the subject. Finally, 13 studies were used to write this study.Results: In reviewing the research background, different studies had used different drugs to prevent shivering after cesarean section. Shivering after spinal anesthesia has been the specific goal of many studies with clinical trial design. Performed interventions in this regard included: intrathecal or intravenous injection of drugs such as magnesium sulfate, hydrocortisone, dexamethasone, ondansetron, ketamine, midazolam, ketamine with midazolam. Opioid drugs such as fentanyl, tramadol, and pethidine have also been reviewed in some studies.Conclusion: Based on various studies, pethidine with unknown and possible mechanism of μ receptors seems to be the best drug in control of Shivering in cesarean section.